Incidence of skeletal fractures after traumatic spinal cord injury: a 10-year follow-up study. (April 2014) - Gifre, Laia; Vidal, Joan; Carrasco, Josep; Portell, Enric; Puig, Josep; Monegal, Ana; Guañabens, Núria; Peris, Pilar
Objective: To analyse the incidence and factors related to the development and clinical evolution of fractures in patients with traumatic spinal cord injury. Design: A retrospective 10-year follow-up study. Setting: Neurorehabilitation centre. Subjects: Sixty-three patients (50M/13F) with a mean age of 36 ± 20 years with recent traumatic spinal cord injury attended over a one-year period (January to December 2000). Main measures: Medical reports were reviewed, evaluating risk factors for osteoporosis, fracture incidence during the 10 years following spinal cord injury, severity (ASIA score) and level of spinal cord injury (paraplegia/tetraplegia), type of lesion (spastic/flaccid), weight-bearing standing activity, and the cause, location and evolution of the fracture. Results: Of the 129 patients attending during the study period, 75 had traumatic spinal cord injury (7 died and 5 had no follow-up). Finally, 63 patients were included. Fifty-four per cent had complete motor injury (ASIA A). Twenty-five per cent of these patients developed fractures, with 2.9 fractures per 100 patient-years. The femur was the most frequent location of the fractures. Fractures were observed 6.4 ± 2.4 years after spinal cord injury (range 2–10 years), all in males. Most fractures (70%) were related to low-impact injuries. Fifty per cent presented with associated clinical complications and only 20% of the patients had received anti-osteoporotic treatment. Spinal cord injury severity was the only risk factor for the development of fractures (complete spinal cord injury (ASIA A)) (RR 4.043; 95% confidence interval (CI) 1.081–23.846, P = 0.037). Conclusion: The incidence of fractures after spinal cord injury is high, with severity and time since spinal cord injury being the main determinants for their development. Fractures were frequently associated with clinical complications. However, the use of anti-osteoporotic treatment was uncommon.